Lactic Acid Bacteria and Histamine Levels of Sie Balu After Gamma Irradiated. - Arham Arham; Nurliana Nurliana; Sugito Sugito (The Faculty of Veterinary Medicine of Syiah Kuala University, 2019)
The presence of lactic acid bacteria (LAB) and histamine in foodstuffs indicate the level of deterioration in the quality of food and cause poisoning. Sie Balu is the Acehnese dried meat preserved by the addition of salt, acid and dried, but the long processing and drying it under the sun can cause microbial contamination in meat products. Irradiation can eliminate bacteria in foodstuffs. This study aimed to determine the amount of LAB and histamine levels of Sie Balu after irradiation doses of 5, 7 and 9 kGy and stored 2 to 4 months. Sie Balu was made of fresh beef 5 kg, dried in the sun to dry, vacuumed and irradiated with gamma rays. The samples for LAB determination cultured in MRS agar and incubated at 37°C for 24 hours. The number of colonies was counted using Total Plate Count. The histamine level of Sie Balu conducted by ELISA. Irradiation did not significantly (P0.05) affect the amount of LAB, but the shelf life significantly (P0.05) affected the amount of LAB in Sie Balu. Extending the shelf life up to 4 months can increase the amount of LAB. Irradiation dose and shelf life had no effect on histamine levels of Sie Balu (P0.05). This study concluded that irradiated Sie Balu cannot be stored for more than two months.